Tolerance to Selenoprotein Loss Differs between Human and Mouse - Santesmasses, Didac (Mol Biol Evol, 2020)
Mouse has emerged as the most common model organism in biomedicine. Here, we analyzed the tolerance to the loss-of-function (LoF) of selenoprotein genes, estimated from mouse knockouts and the frequency of LoF variants in humans. We found not only a general correspondence in tolerance (e.g., GPX1, GPX2) and intolerance (TXNRD1, SELENOT) to gene LoF between humans and mice but also important differences. Notably, humans are intolerant to the loss of iodothyronine deiodinases, whereas their deletion in mice leads to mild phenotypes, and this is consistent with phenotype differences in selenocysteine machinery loss between these species. In contrast, loss of TXNRD2 and GPX4 is lethal in mice but may be tolerated in humans. We further identified the first human SELENOP variants coding for proteins varying in selenocysteine content. Finally, our analyses suggested that premature termination codons in selenoprotein genes trigger nonsense-mediated decay, but do this inefficiently when UGA codon is gained. Overall, our study highlights differences in the physiological importance of selenoproteins between human and mouse.